Myeloid-Derived Suppressor Cells (MDSC) Protect Islet Transplants via B7-H1 Mediated Enhancement of T Regulatory Cells - Chou, Hong-Shiue (2012)
BACKGROUND: Side effects of lifetime immunosuppression for cell transplants often outweigh the benefits, therefore, induction of transplant tolerance is needed. We have shown that cotransplantation with myeoid-derived suppressor cells (MDSC) effectively protect islet allografts from rejection without requirement of immunosuppression. This study was to investigate the underlying mechanisms. METHODS: MDSC were generated by addition of hepatic stellate cells (HpSC) from various stain mice into dendritic cell (DC) culture. The quality of MDSC was monitored by phenotype and function analyses. MDSC mixed with islet allografts were transplanted into diabetic recipients. T cell response was analyzed following transplant by flow and histochemical analyses, and compared to islet alone and islet/DC transplant groups. B7-H1 knockout mice were used to determine the role of B7-H1 on MDSC in regulation of T cell response. RESULTS: Cotransplantation with MDSC (not DC) effectively protected islet allografts without requirement of immunosuppression. This is associated with attenuation of CD8 T cells in the grafts and marked expansion of T regulatory (Treg) cells, which contributed to MDSC-induced T cell hyporesponsiveness. Antigen-specific Treg cells were prone to accumulate in lymphoid organs close to the grafts. Both in vitro and in vivo data demonstrated that B7-H1 was absolutely required for MDSC to exert immune regulatory activity and induction of Treg cells. CONCLUSION: The described approach holds great clinical application potential, and may overcome the limitation of requiring chronic administration of immunosuppression in cell transplants. Understanding the underlying mechanisms will facilitate the development of this novel therapeutic strategy.